Land capability assessment for the sustainable use of the Talomo-Lipadas watershed area an application of the terrain mapping approach - Velasco, Diana Kristina B. (UP in Mindanao, 2004)
The practice of planning in the Philippines is dominated mainly by the use of social, economic and political perspectives. While physical determinants in the production of a viable land use plan have been accorded some importance, there still seems to be a dearth in holistic methods to enable planners to analyze physical data and apply them in a significant and effective manner and scale. This study is an attempt to analyze and integrate the physical attributes of the Talomo-Lipadas Watershed Area (TLWA), and translate these results into a form that can be easily understood and used by planners and other professions with limited geotechnical understanding. In particular, this study - 1) characterizes the general geophysical environment of the Talomo-Lipadas Watershed Area (TLWA) utilizing the terrain approach, 2) develops a set of standards to serve as a basis for establishing the capability of the TLWA to accommodate most forms of land use, 3) establishes the capability of the individual each terrain mapping units in accommodating general land uses, 4) develops general land use recommendations based on the physical character of the study area, and 5) develops land use recommendations by comparing the results of this research to the general land use plan of Davao City. This study shows that the central portions of the watershed, especially the Lipadas lower volcanic footslopes, are the areas that are most accommodating to development in the form of residential, commercial, institutional, industrial and agricultural land uses. Based on the geophysical character of the TLWA, its western, easternmost and southeast sections are more ideally suited as a forest and/or conservation zone. If development within the watershed area is inevitable, then residential, commercial, institutional and industrial land areas should be limited to those terrain mapping units (TMUs) which are highly capable of accommodating these types of development land uses. TMUs which have been computed to have a high and moderate capability of accommodating a conservation and/or forest land use must be excluded as areas for development options in order to secure the over-all geophysical balance of the TLWA, considering that it is the single most important potable water source of Davao City. It is therefore concluded that the current spatial development strategy of the city government warrants proper re-examination, in order to give proper consideration to the geophysical character of the watershed. More stringent rules and regulations must also be put in place to ascertain that the most vulnerable areas of the TLWA are properly protected, and ensure its sustainable use.